Pemberdayaan Santri PPTQ Abi Ummi Boyolali dalam Mencegah dan Menanggulangi Penyebaran Covid-19 - Abid Nurhuda (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
The pandemic has caused a change in the form of activities from direct activities to online activities. On the other hand, educational institutions are allowed to hold learning and teaching activities but with strict health conditions and protocols. One of the educational institutions that carry out the learning and teaching process is the Tahfidzul Qur'an Islamic Boarding School (PPTQ) Abi Ummi Boyolali. Even though they are required to implement strict health protocols, there are still some students who do not implement them. The purpose of this service is to increase the awareness of the students in implementing health protocols. Data collected by interview and observation. The result of this dedication is an increase in the understanding and awareness of the students in implementing health protocols, such as wearing masks, washing hands, and maintaining distance.